Using Predictive Controller to Control a Nonlinear System - Hrbcek, Jozef; Simak, Vojtech; Janota, Ales (Communications - Scientific Letters of the University of Zilina, 2010)
This paper engages in the Model Predictive Control of an Air Pressure system. The Air Pressure system includes a pneumatic and an electronic part. The model of the system was created using a tool for systems identifications. Since the system is nonlinear we can use the model linearization and set the constraints to create the Model Predictive Controller in MATLAB environment. The connectivity between PC and the air pressure system is realized by I/O card MF624. We provided the stability test as well. The PID controller was also designed to compare the results with those obtained from the Model Predictive Controller of the mentioned Air Pressure control system.
Keywords: no keywords